Study design of Soil Retaining Wall Samarinda Tenggarong STA 7+800 s/d STA 7+870 street Samarinda city - GUNAWAN, RENDY (KURVA S JURNAL MAHASISWA, 2016)
Avalanche is the removal of material such as soil or rocks coming down a mountain or mountain slopes. Jalan Poros Samarinda Tenggarong area is an area with tofografi wavy or in the sense hilly, very vulnerable to landslides. In the event of landslides in this area, the access to the landfill (Landfill) in Samarinda and to Tenggarong disconnected. Author only planned Retaining Wall Dimensions, for Planning Dimensions retaining wall locatedÂ on a hill nut using the (Coulomb) to the dimensions of the retaining wall (Retaining wall), the analysis of this construction through phases - phasesÂ such, the actual data collection field (topography and soil investigation) to analyze the shape dimension and the stability of the soil bearing capacity. This construction which will withstand landslides.